Sinapic Acid Attenuates High Blood Pressure Oxidative Stress and Hyperlipidemia in L NAME Induced Hypertensive Rats - B Raja, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Sinapic Acid Attenuates High Blood Pressure Oxidative Stress and Hyperlipidemia in L NAME Induced Hypertensive Rats